The Origin of Onomatopoeia in English and Uzbek Language - Aliboeva Nilufar Makhamatali kizi (International Journal on Integrated Education, 2021)
In this article, the linguistic landscape of the world, the artistic image of each language is unique and multifaceted, the national view of this being, the specific phonetic system of each language and its connection with the features of national articulation.